Implementation of Differentiate Learning to Students With Types of Speech Delay Disorders - Wiranti, Novia; Indahsari, Rima Astuti; Rahmawati, Siti Azizah; Stifani, Yulia; Mashar, Riana (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
This study aims to determine the implementation of Differentiated Learning in institutions, especially those that have students with special needs for speech delay. This research is qualitative research with a case study type for collecting data using observation, interviews, and scrutiny of documents. The data collected is then analyzed using the Miles and Huberman model techniques, namely through data reduction, data display, and drawing conclusions. The research was conducted at the Aisyiyah Bustanul Athfal Kindergarten in Sleman Regency, Special Province of Yogyakarta. The results of the research show: 1) the mechanism for organizing Differentiated Learning in the institution has yet to be carried out under the differentiated learning guideline procedures. 2) Differentiated Learning material delivered is considered necessary while handling the reactions of children with speech delay needs is limited to providing stimulation in the form of speaking training to children with these obstacles. 3) the implementation of integrating Differentiated Learning into the curriculum and learning implementation plan documents and an assessment of Differentiated Learning has yet to be carried out. The Effectiveness of Differentiated Learning has yet to be carried out effectively. It is evidenced by students who are not entirely comfortable in learning, improving skills in terms of hard and soft skills that are not evenly distributed among all children, and the lack of ability to self-reflect, especially for students with speech delay disorders. However, the results of the study indicate that there have been efforts by institutions to apply differentiated learning in learning activities, especially for students with speech delay disorders or barriers. Abstrak Penelitian ini bertujuan untuk mengetahui implementasi Pembelajaran Berdiferensiasi pada lembaga khususnya yang memiliki siswa dengan kebutuhan khusus speech delay. Penelitian ini merupakan penelitian kualitatif dengan jenis studi kasus. Penggalian data menggunakan observasi, wawancara, dan pencermatan dokumen. Data yang telah dikumpulkan kemudian dianalisis menggunakan teknik model Miles dan Huberman, yaitu melalui proses reduksi data, display data, dan penarikan kesimpulan. Penelitian dilakukan pada lembaga Taman Kanak-Kanak Aisyiyah Bustanul Athfal, yang bertempat di Kabupaten Sleman Provinsi Daerah Istimewa Yogyakarta. Hasil penelitian menunjukkan: 1) mekanisme penyelenggaraan Pembelajaran Berdiferensiasi di satuan/lembaga belum terlaksana sesuai dengan prosedur pedoman pembelajaran berdiferensiasi. 2) materi Pembelajaran Berdiferensiasi yang disampaikan merupakan poin – poin yang dianggap penting, adapun penangan terhadap reaksi anak yang memiliki kebutuhan speech delay dilakukan sebatas memberi stimulasi berupa pelatihan berbicara kepada anak yang memiliki hambatan tersebut. 3) pelaksanaan pengintegrasian Pembelajaran Berdiferensiasi dalam kurikulum dan dokumen rencana pelaksanaan pembelajaran serta penilaian terhadap Pembelajaran Berdiferensiasi belum dilakukan. Efektivitas Pembelajaran Berdiferensiasi belum terlaksana secara efektif. Hal ini dibuktikan dengan siswa yang belum seluruhnya merasa nyaman dalam belajar, peningkatan keterampilan baik segi hard skill atau softskill yang belum merata pada keseluruhan anak, dan belum adanya kemampuan merefleksikan diri terkhusus pada siswa dengan gangguan speech delay. Namun hasil penelitian menunjukkan bahwa telah ada upaya dari lembaga untuk menerapkan pembelajaran berdiferensiasi dalam kegiatan pembelajaran terkhusus untuk siswa dengan gangguan atau hambatan speech delay.